Убеждение страхом: роман / Владимир Шитов - Шитов Владимир Кузьмич (Русская бойня, 1998)
Экземпляры: ф.7 (1998) / Инвентарный номер: 40671 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 64 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44